Retranslation in the Malaysian context: the case of two Malay translations of Almayer’s Folly - Nor Idatul Akmar Zulkipli; Haslina Haroon (Penerbit Universiti Kebangsaan Malaysia, 2023)
Retranslation can be understood as a new translation in a particular target language of a text that has already been translated into the same target language. Retranslation is premised on the concept of the difference between the first translation and the subsequent translation. Considering the fact that change is involved in the process of retranslating, one question that arises is about the nature of the changes that take place. In other words, in what way does the retranslation differ from the initial translation? This paper aims to explore this issue via an exploration of two Malay translations of Joseph Conrad’s Almayer’s Folly. Specifically, the paper aims to discuss differences between the two translations and determine the factors that may have influenced the translational choices. In order to carry out the study, the two Malay translations of Almayer’s Folly, Istana Impian (1967) and Kemudi (2016), are compared to their English source text, and the historical context of both translations is explored. The textual analysis identified three main points where the translations differ, i.e. in the treatment of proper names, in the treatment of some English words, and in the treatment of certain expressions. It is also found that these translational choices are not arbitrary. This study underscores the importance of understanding the historical context of a (re)translation, as it is only when a translation is properly contextualised that it becomes clear that translational choices may be motivated by factors outside the text.